POST-COMBUSTION COAL DESULFURIZATION Review - Silky Amanda Yuniar; Edy Nursanto; Rika Ernawati (Eksergi, 2020)
The sulfur content in coal ranges from 0.5 to 5%, and it is an impurity that must be removed before burning coal, due to the toxic effects and acid rain caused by SO2 gas generated from sulfur oxidation. Sulfur cleaning technology can be carried out on coal before combustion (pre-combustion), and can reduce the inorganic sulfur content by up to 50%; however, it cannot reduce the organic sulfur content. Therefore, the industry relies on post-combustion desulfurization to remove SO2 from the gas from coal combustion. The aim of the coal desulfurization review is to direct desulfurization research to be efficient and effective, as well as to be environmentally friendly. Sulfur in coal consists of organic sulfur and inorganic sulfur. Coal inorganic sulfur consists of pyrite (FeS2), sulfate, and sulfide. The largest composition is pyrite. Organic sulfur consists of hetero-atomic and heterocyclic (thiophenic) macromolecules that bind N and O atoms, aromatic sulfides, and aromatic disulfides (small amounts). Inorganic sulfur can easily be separated from coal by means of flotation, microwave energy, magnetic forces, ultrasonic energy, and as well as microorganisms. Meanwhile, organic sulfur cannot be separated from coal by using the methods used in the inorganic sulfur separation process. Organic sulfur can be removed by chemical and biodesulfurization, however, this process is inefficient for industrial scale. The most recommended method is the absorption of SO2 gas in the gas from coal combustion, or post-combustion desulfurization. Various methods have also been investigated to separate SO2 gas, and more details will be described in this paper.